Flipped learning in Spanish as a foreign language: effects of instructional design on speaking interaction skills - Sofía Sooyeon Choi; Cristina Herrero-Fernández; Ocarina Masid Blanco (Asian-Pacific Journal of Second and Foreign Language Education)
Abstract This study explores the potential of a pedagogical model based on Flipped Learning (FL) to support the development of speaking interaction skills in Spanish as a foreign language (SFL). A preliminary instructional framework grounded in FL principles was designed specifically for A2-level SFL learners, and its implementation was examined through a pre-experimental quantitative research approach. The study involved 20 Singaporean students enrolled in an A2-level SFL course who participated in an 11-week intervention using FL methodologies. Data collection included pre- and posttests focused on the speaking interaction component of the DELE (Diploma de Español como Lengua Extranjera) A2 exam. To address the research question—whether students' speaking interaction skills showed measurable changes after applying the FL model—the Wilcoxon signed-rank test was employed. Results indicated improved speaking interaction skills, with mean scores increasing from 2.400 (SD = 1.536) in the pretest to 3.600 (SD = 1.465) in the posttest. Improvements were also observed in linguistic skills and task completion. While these findings are preliminary, they suggest that the FL model shows promise as a structured and interactive approach to enhancing speaking interaction skills in non-immersive SFL learning contexts. This study offers insights that may inform future pedagogical approaches for foreign language teachers aiming to foster speaking interaction skills in similar settings.